Exploring perceptions of the COVID-19 infodemic (Journal of EAHIL, 2021)
The flow of information about Covid-19 has caused an infodemic worldwide. This paper presents results from a survey study conducted in Finland in the spring of 2020. The aim is to explore the most important sources or channels for corona-related information in that early stage of the pandemic, as well as how the amount of information was perceived and which emotions were related to this information among 208 respondents aged 30 years and over. News media, social media and official information were most important. The amount of information was perceived as suitable by many, but others experienced an overload, and the obtained information largely raised negative emotions including concern, fatigue and irritation. The results hence largely follow earlier studies.